Basic marketing research using Microsoft Excel data analysis / Alvin C. Burns ; Ronald F. Bush - Burns, Alvin C.
Basic Marketing Research uses an Excel add-in software for data analysis, an integrated case, and experiential learning exercises to present a concise introduction to market research fundamentals. This text also provides readers with resources they can use in their careers.